2021
DOI: 10.3390/antibiotics10060651
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of α-Monolaurin and Butyrate Supplementation on Broiler Performance and Gut Health in the Absence and Presence of the Antibiotic Growth Promoter Zinc Bacitracin

Abstract: The use of antibiotic growth promoters (AGP) is common practice to improve broiler production and performance. The use of AGP is under discussion as it can induce bacterial resistance. The purpose of this study was to determine the impact of removing AGP from broiler feed and study the effect of feed additives. For those countries where in-feed AGP are still permitted, the effect of the products in the presence of AGP was evaluated. Half the number of male broilers received a diet free of AGP, whereas the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…CCP possess significant antioxidant and anti-aging activities (33), it could enhance the immune capacity of the body (14,15). In the present study, the pigeons fed the 275 mg/kg CSB and 110 mg/kg CCP diet showed an increase in final BW and ADG efficiency in comparison with the CON group, which is consistent with the findings of a previous study (34). Although studies have demonstrated the regulation of butyrate on fat accumulation (35,36) the difference associating with different concentrations was not clearly defined.…”
Section: Discussionsupporting
confidence: 92%
“…CCP possess significant antioxidant and anti-aging activities (33), it could enhance the immune capacity of the body (14,15). In the present study, the pigeons fed the 275 mg/kg CSB and 110 mg/kg CCP diet showed an increase in final BW and ADG efficiency in comparison with the CON group, which is consistent with the findings of a previous study (34). Although studies have demonstrated the regulation of butyrate on fat accumulation (35,36) the difference associating with different concentrations was not clearly defined.…”
Section: Discussionsupporting
confidence: 92%
“…The linear effect was more obvious in crypt goblet counts. These results were in agreement with previous studies reporting alteration in the intestinal goblet cell counts with the supplementation of fatty acid blends to broilers ( Amer et al, 2020 ; Letlole et al, 2021 ). However, some authors reported no treatment effect of fatty acid mixtures on goblet cell counts in the intestine of either healthy or stressed animals ( Abdelli et al, 2020 ; Lin et al, 2022 ).…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, under healthier conditions, some earlier studies did not show statistical changes in the intestinal villi and crypt characteristics of broilers fed diets supplemented with different short- and medium-chain fatty acid blends at levels ranging from 0.03 to 0.3% ( Khatibjoo et al, 2018 ; Liu et al, 2021 ; Lin et al, 2022 ). In other reports, however, broilers fed fatty acid blends (0.2–0.5%) showed beneficial effects on intestinal structure ( Amer et al, 2020 ; Dauksiene et al, 2021 ; Letlole et al, 2021 ), and such effects were more pronounced under disease challenge ( Santos et al, 2019 ; Abdelli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
“…This was supported by the lower fecal score in the ML+PEDV group. CD ratio in the duodenum, jejunum and ileum were increased with ML addition (22). The beneficial effect of ML in gut health and development may be due to the fact that ML could promote the production of energy by intestinal cells, and further promote the intestinal integrity in piglets (23).…”
Section: Discussionmentioning
confidence: 96%
“…MaxQuant software was employed to process all the raw MS/MS spectra using the Sus scrofa database (22,191 sequences) downloaded from UniProtKB database on the November 10, 2018. The parameters were set as described previously (16).…”
Section: Protein Identification and Data Analysismentioning
confidence: 99%